2016
DOI: 10.3758/s13428-016-0772-7
|View full text |Cite
|
Sign up to set email alerts
|

One tamed at a time: A new approach for controlling continuous magnitudes in numerical comparison tasks

Abstract: Non-symbolic stimuli (i.e., dot arrays) are commonly used to study numerical cognition. However, in addition to numerosity, non-symbolic stimuli entail continuous magnitudes (e.g., total surface area, convex-hull, etc.) that correlate with numerosity. Several methods for controlling for continuous magnitudes have been suggested, all with the same underlying rationale: disassociating numerosity from continuous magnitudes. However, the different continuous magnitudes do not fully correlate; therefore, it is impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
99
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(107 citation statements)
references
References 21 publications
5
99
0
Order By: Relevance
“…This point has been recently demonstrated even in the subitizing range. A work by Salti et al (2017) revealed that different manipulations of continuous magnitudes influence performance in a non-symbolic Stroop-like task with numerosities in the subitizing range (e.g., 2-4; for an example of a nonsymbolic Stroop-like stimuli, see Fig. 3B).…”
Section: Evidence Supporting Holistic Processing Of Numerosity and Comentioning
confidence: 99%
See 2 more Smart Citations
“…This point has been recently demonstrated even in the subitizing range. A work by Salti et al (2017) revealed that different manipulations of continuous magnitudes influence performance in a non-symbolic Stroop-like task with numerosities in the subitizing range (e.g., 2-4; for an example of a nonsymbolic Stroop-like stimuli, see Fig. 3B).…”
Section: Evidence Supporting Holistic Processing Of Numerosity and Comentioning
confidence: 99%
“…However, dissociating perimeter and area from numerosity ignores the possibility that participants rely on other magnitudes or even switch between them. Salti et al (2017) detailed an elaborate taxonomy showing a more complex relationship between continuous magnitudes and numerosity. According to this taxonomy, the inter-correlations between the different continuous magnitudes make the dissociation between numerosity and all continuous magnitudes far from trivial.…”
Section: R33 Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have to some extent arrived at different conclusions, sometimes 130 finding that numerosity, and sometimes that area judgement is more subject to interference, 131 possibly as a consequence of the above mentioned factor of degree of change / 132 discriminability. Indeed when total surface area was claimed to be dominant over the 133 numerical dimension, larger changes in the unattended area dimension were used (Hurewitz 134 et al, 2006;Leibovich et al, 2016b), however when the range of ratio variation across 135 dimension was physically equated, the opposite conclusion was reached (Nys and Content,136 2012; Salti et al, 2016). Indeed the interference arising from numerosity changes in total 137 surface area comparisons was reported to be either similar or stronger with respect to the 138 total surface area interference during numerosity judgments, both when testing the subitizing 139 range (Salti et al, 2016) and much higher numerosities (Nys and Content, 2012).…”
mentioning
confidence: 99%
“…Indeed when total surface area was claimed to be dominant over the 133 numerical dimension, larger changes in the unattended area dimension were used (Hurewitz 134 et al, 2006;Leibovich et al, 2016b), however when the range of ratio variation across 135 dimension was physically equated, the opposite conclusion was reached (Nys and Content,136 2012; Salti et al, 2016). Indeed the interference arising from numerosity changes in total 137 surface area comparisons was reported to be either similar or stronger with respect to the 138 total surface area interference during numerosity judgments, both when testing the subitizing 139 range (Salti et al, 2016) and much higher numerosities (Nys and Content, 2012). However, 140 none of these studies took into account the differences that may exist between the 141 perceptual discriminability of different features, as a result of which using identical physical 142 ratios across dimensions may not necessarily translate into equating perceptual salience.…”
mentioning
confidence: 99%